The Pragmatic perspective in Iben Djinni’s book ‘El khassais’ - Benmicia, Rafika (Journal of Human Sciences, 2020)
This study aims at demonstrating some of The Pragmatic perspective in Iben Djinni’s book ‘El khassais’. These perspective are considered to be outstanding ideas for the ancient Arabic course of the language and also a solid base for the modern and contemporary course of pragmatics. Those notions consist of the elements of the communicative process, the function of the language, the relationship between the function and the structure, and the linguistic competence and the communicative competence . Thus, it is obvious that the modern and the contemporary occident course of the language is just an extension of the ancient Arabic one, and there is no Epistemological rupture between them despite of the differences in the methods of presentation of the ideas, the methodology of the analysis and the purpose from the study.